High-power microwave radiation by summation of the radio signals at the output of resonance shapers; Soviet Physics - Technical Physics; Vol. 16, № 10 - Novikov S. A. Sergey Avtonomovich; Razin S. V.; Chumerin P. Yu.; Yushkov Y. G. Yuri Georgievich (1990, 1990)
В фонде НТБ ТПУ отсутствует